Feasibility of non‐invasive measurement of central blood pressure and arterial stiffness in shock. (22nd May 2021) - Markakis, Konstantinos; Pagonas, Nikolaos; Georgianou, Eleni; Zgoura, Panagiota; Rohn, Benjamin J.; Bertram, Sebastian; Seidel, Maximilian; Bettag, Sebastian; Trappe, Hans‐Joachim; Babel, Nina; Westhoff, Timm H.; Seibert, Felix S.
Abstract: Background: Patients in haemodynamic shock are in need for an intensive care treatment. Invasive haemodynamic monitoring is state of the art for these patients. However, evolved, non‐invasive blood pressure monitoring devices offer advanced functions like the assessment of central blood pressure and arterial stiffness. We analysed the feasibility of two oscillometric blood pressure devices in patients with shock. Methods: We performed a monocentre prospective study, enrolling 57 patients admitted to the intensive care unit (ICU), due to septic and/or cardiogenic shock. We assessed invasive and non‐invasive peripheral and central blood pressure <24 hours and 48 hours after admission on the ICU. Additional haemodynamic parameters such as pulse wave velocity (PWV), augmentation pressure and augmentation index were obtained through Mobil‐o‐Graph PWA (IEM) and SphygmoCor XCEL (AtCor Medical). Results: A complete haemodynamic assessment was successful in all patients (48) with the Mobil‐o‐Graph 24 hours PWA and in 29 patients with the SphygmoCor XCEL ( P  = .001), when cases of death or device malfunction were excluded. Reasons for failure were severe peripheral artery disease, haemodynamic instability, oedema and agitation. Invasive blood pressure showed a sufficient correlation with both devices; however, large differences between invasive and non‐invasive techniques were recorded in Bland‐Altmann analysis ( P  < .05 for all parameters). PWV differed between the two devices. Conclusion: Non‐invasive peripheral blood pressure measurement remains a rescue technique. However, non‐invasive assessment of arterial stiffness and central blood pressure is possible in patients with septic or cardiogenic shock. Further studies are required to assess their clinical significance for patients in shock.